CNS Depressant activity of ethanol extract of sterculia guttata seeds in mice - Katade, S. R.; Misar, Ashwini V.; Mujumdar, Arvind M.; Phalgune, U. D.; Wakharkar, R. D.; Deshpande, N. R. (Indian Journal of Pharmaceutical Sciences, 2009)
Shade dried, powdered seeds of Sterculia guttata were extracted using a Soxhlet extractor with ethanol. Ethanol was removed under reduced pressure and dried to obtained crude extract. This extract was evaluated for its effect on behavioral changes, exploratory activity and barbiturate-sleeping time, using appropriate standard methods in mice. The extract exhibited dose-dependent CNS depressant activity.
Keywords: Barbitone sodium; CNS depressant activity; pentobarbitone sodium; Sterculia guttata Roxb.; Swiss albino mice

Sesquiterpene lactone, a potent drug molecule from artemisia pallens wall with anti-inflammatory activity - Ruikar, Anjali D.; Misar, Ashwini V.; Jadhav, Ravindra B.; Rojatkar, Supada R.; Mujumdar, Arvind M.; Puranik, Vedavati G.; Deshpande, Nirmala R. (Arzneimittel-Forschung-Drug Research, 2011)
The present study was carried out to investigate the anti-inflammatory activities of bioactive secondary metabolites of Artemisia pallens Wall, an aromatic herb from family Asteraceae. The results provide evidence for the topical anti-inflammatory properties of Artemisia pallens Wall. The compounds were isolated from the acetone extract of the plant material. The isolates were tested on Swiss albino mice using 12-O-tetradecanoyl phorbol-13-acetate (TPA) induced ear edema. One of the molecules from the extract indicated potent anti-inflammatory activity equivalent to indometacin (CAS 53-86-1). Elucidation of the molecular structures by single crystal x-ray diffraction studies revealed the conformational differences that the six membered rings in both the molecules are at an angle of 28.79 degrees. Presence of hydroxy function for compound 2 may be responsible for higher potency.
Keywords: Anti-inflammatory activity; Artemisia pollens; Asteraceae; Mice; Single crystal x-ray structure

First synthesis of podocarflavone A and its analogs and evaluation of their antimycobacterial potential against mycobacterium tuberculosis with the support of virtual screening - Puranik, Ninad V.; Swami, Sagar; Misar, Ashwini V.; Mamgain, Ritu; Gulawani, Swapnaja S.; Dhiman, Sarkar; Srivastava, Pratibha (Natural Product Research, 2022)
The first synthetic route developed for Podocarflavone A reported from Podocarpus macrophyllus and its analogs in 7 steps. Computational analysis for binding with the pantothenate kinase (3AVO) of Mycobacterium tuberculosis showed their docking score (ds) in the range of -8.9 to -9.3 Kcal/mol. MD simulations delineated the stability of the protein-ligand complexes in the TIP3P model. MMGBSA and MMPBSA values of 8d were -42.46 Kcal/mol and -14.58 Kcal/mol, respectively. Further in-vitro antitubercular screening of compounds 8a, 8d, and 8e against M. tuberculosis H37Ra using XRMA protocol exhibited promising antimycobacterial activity with IC50 values 21.82 mu g/mL, 15.55 mu g/mL, and 16.56 mu g/mL, respectively. Compounds 8a, 8d, and 8e showed antibacterial activity with IC50 values 41.56 mu g/mL, 24.72 mu g/mL, and 72.45 mu g/mL respectively against the Staphylococcus aureus. 8a and 8d showed inhibition with IC50 values 39.6 mu g/mL and 27.64 mu g/mL, respectively, against Bacillus subtilis. The present study could help in the further development of lead molecules against tuberculosis.
Keywords: and MMGBSA; antimycobacterial activity; docking; MD simulations; MMPBSA; Podocarflavone A synthesis